THE ROLE OF SELF-EFFICACY IN MEDIATING THE EFFECT OF NEED FOR ACHIEVEMENT, FAMILY ENVIRONMENT ON ENTREPRENEURIAL INTENTION IN MANAGEMENT STUDENTS AT MERCU BUANA UNIVERSITY - Himawan, Sigit; Aima, M. Havidz (Dinasti Publisher, 2021)
This study aims to analyze the role of self-efficacy in mediating the effect of need for achievement, family environment on entrepreneurial intention in Mercu Buana University Management Students. The sample in this study was obtained 210, using the Slovin formula. This study uses a quantitative analysis approach with the SEM-PLS data analysis method. The results show that the need for achievement has a significant effect on self-efficacy, the need for achievement has a significant effect on entrepreneurial intention, the family environment has a significant effect on self-efficacy, the family environment has no significant effect on entrepreneurial intention, self-efficacy has a significant effect on entrepreneurial intention, need for achievement and family environment simultaneously have a significant effect on self-efficacy, need for achievement, family environment and self-efficacy simultaneously have a significant effect on entrepreneurial intention, self-efficacy significantly mediates need for achievement on entrepreneurial intention, and self-efficacy significantly mediates family environment on entrepreneurial intention.